The important role of website characteristics (E-Commerce) and service quality on the intensity of customer purchases - Kurniawan Kurniawan; Supriandi Supriandi; Agung Maulana; Idrus Kurniawan (International Journal of Data and Network Science)
This study observed more than 150 respondents in the digital trading environment, explaining how the important role of website characteristics and service quality influences customer purchase intensity. PLS-SEM analysis of the data was performed using SMARTPLS version 3 software. After that, the samples were collected through an online questionnaire by setting several criteria to make the resulting perceptions accurate. The study's findings show that while a website's features have a big impact on customer trust, customer loyalty, and purchase intensity can all be directly impacted by the quality of the product or service offered. However, unfortunately, customer trust and satisfaction cannot mediate website characteristics in their influence on customer purchase intensity. Overall, this study expands the understanding in the field of trade that service quality and website characteristics significantly influence increasing customer buying intensity.